On Recovering the Structure of Affect - Kapoor, Ashish; Czerwinski, Mary; MacLean, Diana Lynn; Zolotovitski, Alex (Humaine Association Conference on Affective Computing and Intelligent Interaction (ACII), 2013, 2013)
This paper presents novel human computation experiments geared towards uncovering the structure of affect. Using Mechanical Turk workers across 2 separate studies, we empirically verified some of the popular beliefs about the structure of affect, but also provide some new evidence. We replicate and reveal not only the statistical structure of the dimensions of affect, but also the effect of cultural influences. We close with a proposition for a framework for doing this kind of large scale research and provide recommendations and opportunities for innovations in research around emotional theory.